PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN (STUDI KLAUSAL DI PT. ASURANSI CENTRAL ASIA) - Dewi Ramayani Ratningsyam; Erwansyah Sjarief (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2022)
Asuransi Central Asia. Not infrequently the existence of companies that have advanced collapsed, just because the commitment of employee organizations decreases from day by day. When an employee feels satisfaction in working, of course, he will try as much as possible with all his ability to complete work tasks. Thus the organizational commitment and work results of employees increase optimally.This research uses the path analysis method. The author collected data with a questionnaire of 100 respondents. Respondents are employees of PT Asuransi Central Asia Marketing. Previously tested the instrument using 30 respondents, then testing the analysis requirements using the normality test, linearity test and, homogeneity test.Based on the results and findings above, it can be concluded that the level of quality of Organizational Commitment is influenced by the Leadership Style, Work Environment and Job Satisfaction. Therefore, if the quality of Leadership Style, Work Environment and Job Satisfaction is improved, it will be able to improve the quality of the Organizational Commitment of employees of PT Asuransi Central Asia